Local FK506 delivery at the direct nerve repair site improves nerve regeneration. Issue 5 (23rd August 2019) - Davis, Brett; Hilgart, David; Erickson, Sierra; Labroo, Pratima; Burton, Joshua; Sant, Himanshu; Shea, Jill; Gale, Bruce; Agarwal, Jay
Abstract: Introduction: The objective of this study is to assess the efficacy of local tacrolimus (FK506) delivery to improve outcomes in the setting of nerve transection injury. Methods: FK506 embedded poly(lactide‐co‐caprolactone) films capable of extended, localized release of FK506 were developed. FK506 rate of release testing and bioactivity assay was performed. Mouse sciatic nerve transection and direct repair model was used to evaluate the effect extended, local delivery of FK506 had on nerve regeneration outcomes. Results: Linear release of FK506 was observed for 30 days and released FK506 matched control levels of neurite extension in the dorsal root ganglion assay. Groups treated with local FK506 had greater gastrocnemius muscle weight, foot electromyogram, and number of axons distal of the repair site than non‐FK506 groups. Discussion: Results of this study indicate that extended, localized delivery of FK506 to nerve injuries can improve nerve regeneration outcomes in a mouse sciatic nerve transection and repair.